Comparative Social Policy Analysis in the EU at the Brink of a New Era. Issue 4 (8th August 2017) - Vandenbroucke, Frank
Abstract: Comparative policy analysis plays an important role in the EU: European social policy, as it developed from the 2000s, is intrinsically interwoven with comparative social policy analysis, notably in the context of the Open Method of Coordination (OMC). A review of the role of comparative social policy analysis in the OMC highlights a number of long-standing challenges, which are discussed in the first section of the paper. Do EU member states commit themselves to a real "burden sharing" with regard to the agreed objectives? How can we effectively mainstream social policy objectives into the EU's economic and budgetary governance? How can we assess the comparative efficiency of EU welfare states? These challenges have a political, a scientific and a technical (data-related) nature. They underscore the necessity of in-depth, shared and validated comparative social policy analysis of member states' policies. The second section of the paper explains that we may be entering a new era, given the reform agenda for the Economic and Monetary Union set out by the so-called Five Presidents' Report; these reforms, if implemented, may lead to important spill-over effects in the domain of European social policy, with new demands for comparative social policy analysis. The third section zooms in on the related challenges for the statistical capacity of the EU and the need to invest in the development of reliable and comparable data.